Pendidikan karakter membentuk insan yang unggul - Laras Novita Sari; Dewi Yana (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2026)
Character education serves as a fundamental foundation in shaping a nation’s high-quality character without neglecting essential social values such as tolerance, solidarity, mutual cooperation, helpfulness, and respect. Character education fosters outstanding individuals who not only possess strong cognitive abilities but also demonstrate moral integrity and personal qualities that enable them to achieve meaningful success.This study employs a qualitative approach by analyzing secondary data and conducting a comprehensive literature review as the primary method to examine how character education contributes to the formation of superior individuals. The secondary data utilized in this research include official reports, academic publications, and relevant documents related to the research topic.The findings of this study indicate that education, both formal and informal, plays a highly strategic role in developing culture and strengthening character education itself. Therefore, the expected character formation cannot rely solely on schools but must also be nurtured within family life and the broader community. Through an integrated character education system implemented across these domains, future Indonesian generations can develop into outstanding individuals shaped by strong moral values and holistic educational processes